Omni Channel Strategy in online retailing: The case of Magestore = Chiến lược bán hàng đa kênh trong bán lẻ trực tuyến: trường hợp của Magestore - Nguyễn, Trọng Phương (2020)
Aims of researchFacing the urgent need to promote businesses to improve their capacity and competitiveness, the study and application of retail solutions in e-commerce for businesses in Vietnam is necessary. On that basis, the content of the thesis focuses on the following main tasks:Systemize to clarify some issues of E-commerceClarify the definitions, concepts, theoretical methods of Omnichannel. Assessing the necessity of Omnichannel retailing and Omnichannel strategy. Retailers that purchased Magestore’s omnichannel solutions. Analyze the situation Omnichannel strategy in Magestore.•Research potentials, opportunities, difficulties as well as challenges when applying Omnichannel for Magestore. Analyze Magestore omnichannel solutions and their supporting services. Recommendations and solutions for Magestore